Secondary organizing pneumonia after recovery of mild COVID‐19 infection. Issue 1 (5th October 2021) - Golbets, Evgeny; Kaplan, Alon; Shafat, Tali; Yagel, Yael; Jotkowitz, Alan; Awesat, Jenan; Barski, Leonid
Abstract: A 36‐year‐old male with diffuse large B‐cell lymphoma on maintenance rituximab therapy presented to the emergency department with high fever and fatigue. A chest X‐ray showed a lobar infiltrate, 40 days before admission the patient suffered from a mild coronavirus disease 2019 (COVID‐19) infection and fully recovered. PCR nasopharyngeal swab was negative for COVID‐19. Comprehensive biochemical, radiological, and pathological evaluation including 18‐fluorodeoxyglucose positron emission tomography with computed tomography and transbronchial lung biopsy found no pathogen or lymphoma recurrence. Treatment for pneumonia with antibiotic and antifungal agents was nonbeneficial. A diagnosis of secondary organizing pneumonia (OP) was made after pneumonia migration and a rapid response to corticosteroids. OP secondary to a viral respiratory infection has been well described. Raising awareness for post‐COVID‐19 OP has therapeutic and prognostic importance because those patients benefit from steroid therapy. We believe the condition described here is underdiagnosed and undertreated by doctors worldwide. Because of the ongoing global pandemic we are now encountering a new kind of patient, patients that have recovered from COVID‐19. We hope that this case may contribute to gaining more knowledge about this growing patient population.